Mechanical responses of a-axis GaN nanowires under axial loads. (30th January 2018) - Wang, R J; Wang, C Y; Feng, Y T; Tang, Chun
Abstract: Gallium nitride (GaN) nanowires (NWs) hold technological significance as functional components in emergent nano-piezotronics. However, the examination of their mechanical responses, especially the mechanistic understanding of behavior beyond elasticity (at failure) remains limited due to the constraints of in situ experimentation. We therefore performed simulations of the molecular dynamics (MD) of the mechanical behavior of [ 1 2 ̄ 10 ] -oriented GaN NWs subjected to tension or compression loading until failure. The mechanical properties and critical deformation processes are characterized in relation to NW sizes and loading conditions. Detailed examinations revealed that the failure mechanisms are size-dependent and controlled by the dislocation mobility on shuffle-set pyramidal planes. The size dependence of the elastic behavior is also examined in terms of the surface structure determined modification of Young's modulus. In addition, a comparison with c -axis NWs is made to show how size-effect trends vary with the growth orientation of NWs.